How is the answer 6 when I keep getting the answer 9.16

How is the answer 6 when I keep getting the answer 9.16


[tex]How is the answer 6 when I keep getting the answer 9.16[/tex]


Leave a Reply 5

Your email address will not be published. Required fields are marked *


cruzsuarezjanca

cruzsuarezjanca

Hmm, I think it's 3.9. Hope this helps

paulesparsa6

paulesparsa6

1. 4 (6 + 7) is the same as (4 • 6) + (4 • 7)
    X = 4
2. 6 • 45 = 270
a. 270, (6 • 40) + (6 • 5) = 240 + 30 = 270
b. 210, (6 • 40) - (6 • 5) = 240 - 30 = 210
c. 270, (6 • 50) - (6 • 5) = 300 - 30 = 270
    A. 270, C. 270
3. 6m + 7n + 5m - 3n, combine like terms, 6m + 5m = 11m, 7n - 3n = 4n
    B. 11m + 4n
4. 2y^3 - 4y^2 + y + y^3, exponents tell you what are like terms
    C. 2y^3 and y^3
5. 4x^3 - 3x^2 + x + 3x^3, combine like terms, then put in descending order
    D. 7x^3 - 3x^2 + x

Jaressayf4466

Jaressayf4466

I agree with Derek and disagree with  What if you want to do it the long way and use the distributive property and distribute the 2 first? You would do: 8 / (4+4) = 1.

Or does the distributive property suddenly no longer apply?

That's what I would say proves that 1 is correct.

I trust Morgan because she's had a math class this decade.

Wikipedia says you hate America if you get 16.

Step-by-step explanation:

Wanna chat add me as a friend OR COME TO SANP (ADAMBELAL839)

averystricker7837

averystricker7837

0.56

Step-by-step explanation:

5.6 ÷ 10

When dividing by ten, move the decimal point one position to the right:

0.56

That is your answer because you were Dividing by Ten and so the worth of that number is lowered by ten or one decimal position.

Hope this helps!

Have a nice day!

If you find my answer helpful

Pls consider marking my answer as Brainliest! It would mean a lot!

iamsecond235p318rq

iamsecond235p318rq

The value of given expression is 6.

Step-by-step explanation:

Given expression is;

[tex]\sqrt{5x^2-(-x^4)}[/tex]

We have to solve the expression when x = -2

Putting x = -2 in the given expression,

Solution = [tex]\sqrt{5(-2)^2-(-(-2)^4))}\\[/tex]

Solution = [tex]\sqrt{5(4) - (-16)[/tex]

Solution = [tex]\sqrt{20+16}[/tex]

Solution = [tex]\sqrt{36}[/tex]

Taking square root of 36

Solution = 6

Thus,

[tex]\sqrt{5x^2-(-x^4)}[/tex] = 6

Hence,

The value of given expression is 6.